Mycosphaerella leaf spot diseases of bananas: present status and outlook: Proceedings of the 2nd international workshop on Mycosphaerella leaf spot diseases held in San José, Costa Rica, 20-23 may 2002 - Jacome, L.; Lepoivre, P.; Martin, D.; Ortíz, R.; Escalant, J-V. (2003)
Thriteen years after the 1st international workshop on Sigatoka diseases of Banana held in San José, Costa Rica, in March 1989, the present proceedings offer an overview of the current situation regarding Mycosphaerella leaf spot diseases at the global level.